L'Amérique septentrionale et les Peaux-Rouges, explorations, impressions de voyage, scènes de mœurs indigènes - Vattemare, H. (Hippolyte), d. 1882.; Catlin, George, 1796-1872.; Möllhausen, Balduin, 1825-1905.; Milton, William Fitzwilliam, Viscount, 1839-1877. (Paris, Hachette, 1881)
An abridgment of three works: "The Northwest passage by land . By Viscount Milton . and W. B. Cheadle"; "Tagebuch einer Reise vom Mississippi nach den Küsten der Südsee. Von Balduin Möllhausen"; and "Letters and notes on the manners, customs and conditions of the North American Indians. By Geo. Catlin." Mode of access: Internet.